Eccentric Harmonic Index for the Cartesian Product of Graphs - Kamel Jebreen; Muhammad Haroon Aftab; M. I. Sowaity; B. Sharada; A. M. Naji; M. Pavithra (Journal of Mathematics)
Suppose ρ is a simple graph, then its eccentric harmonic index is defined as the sum of the terms 2/ea+eb for the edges vavb, where ea is the eccentricity of the ath vertex of the graph ρ. We symbolize the eccentric harmonic index (EHI) as He=Heρ. In this article, we determine He for the Cartesian product (CP) of particularly chosen graphs. Lower bounds for He of the CP of the two graphs are established. The formulas of EHI for the Hamming and Hypercube graphs are obtained. These obtained formulas can be used in QSAR and QSPR studies to get a better understanding of their applications in mathematical chemistry.